2021
DOI: 10.1038/s41467-020-20531-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus(III)-assisted regioselective C–H silylation of heteroarenes

Abstract: Heteroarenes containing carbon–silicon (C–Si) bonds are important building blocks that play an important role in the construction of natural products, pharmaceuticals, and organic materials. In this context, the C–H silylation of heteroarenes is a topic of intense interest. Indole C–H silylation can preferentially occur at the nucleophilic C3 and C2 position (pyrrole core), while accessing the C4-C7 positions (benzene core) of the indole remains highly challenging. Here, we show a general strategy for the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…In 2021, the Shi group reported an efficient method for the regioselective C7 silylation of indoles 23 assisted by a phosphine-directing group in the presence of a palladium catalyst under oxidative conditions, whilst avoiding the addition of any exogenous ligands (Scheme 7 ). 18 The key to obtaining a high level of regioselective silylation was the appropriate choice of an N -protected phosphine directing group. It was found that the N -P t Bu 2 group was the best choice as a directing group for achieving both high reactivity and selectivity in this reaction.…”
Section: Silylation Of C–h Bonds Through Organometallic Intermediatesmentioning
confidence: 99%
“…In 2021, the Shi group reported an efficient method for the regioselective C7 silylation of indoles 23 assisted by a phosphine-directing group in the presence of a palladium catalyst under oxidative conditions, whilst avoiding the addition of any exogenous ligands (Scheme 7 ). 18 The key to obtaining a high level of regioselective silylation was the appropriate choice of an N -protected phosphine directing group. It was found that the N -P t Bu 2 group was the best choice as a directing group for achieving both high reactivity and selectivity in this reaction.…”
Section: Silylation Of C–h Bonds Through Organometallic Intermediatesmentioning
confidence: 99%
“…Recently, we have reported the palladium-catalyzed P­(III)-directed C7-selective C–H silylation of indoles 5 with hexamethyldisilane using 2,5-dimethyl-1,4-benzoquinone (DMBQ) as an external oxidant (Scheme ). Diverse C7-silylated indoles 24 were constructed efficiently, exhibiting broad functional group compatibility. In addition, this developed strategy could also be extended to C–H germanylation with hexamethyldigermane.…”
Section: Functionalization At C7mentioning
confidence: 99%
“…We found that the diverse indoles 42 bearing pivaloyl groups at the C3-position were also capable of participating in C–H borylation at C4-position to access the corresponding borylated indoles 43 in the presence of simple BBr 3 (Scheme ). The choice of the N -Ts group in the indole substrates as a protecting group showed the best reactivity.…”
Section: Functionalization At C4mentioning
confidence: 99%
“…Transformative functionalization of prevalent heteroarenes is an attractive strategy to access valuable synthons with the original heterocyclic skeletons having high synthetic and medicinal utility. Among various functionalities being able to be installed into the heteroaromatics, a silyl group offers special benefits in that it can serve either as a versatile intermediate for further oxidative conversions or as a robust final-stage motif in pharmaceutical, material, and polymer science. In this context, a number of site-selective silylation transformations of heteroarenes were developed by employing readily available silyl sources such as hydrosilanes, silylboranes, or silyl cations. , In this line, transition-metal-catalyzed C–H silylation offers an attractive route to silylated compounds.…”
mentioning
confidence: 99%